Post-human as an emerging paradigm in information science - Monteiro, Silvana Drumond; Vignoli, Richele Grenge [UNESP]; De Almeida, Carlos Cândido [UNESP] (Universidade Federal da Paraíba, 2020)
he post-human evidence as a new paradigm in Information Science to be investigated is studied. From the rejection of binary views between subject and object, in general, and especially between humans and machines, and with the advance of information and information technologies, several disciplines and philosophies are dealing with this new contemporary scenario. Thus, after a critical literature review, it was identified in the Cybernetics the genesis of the post-human, for presenting a concept of dematerialized information and an ontology of similarity between humans and machines, and having the cyborg as an image of this reality. The post-human, superintelligence and transhuman concept was approached to present some characteristics of the informational subject, as the post-human concept has several spectra of hybridization between people and machines. Thus, it is intended to dodge the centrality of the human being as someone endowed with high cognitive capacities in relation to other beings and machines and to reflect on an interdisciplinary thinking in order to understand new sociotechnical phenomena.
O pós-humano como paradigma emergente na ciência da informação
Keywords: Information Science; Informational subject; Paradigm; Post-human; Superintelligence; Transhuman